FORMATION OF THE BEEKEEPING SECTOR IN KASHKADARYA REGION ON THE BASIS OF CLUSTER PRINCIPLES AND LONG-TERM DEVELOPMENT STRATEGY - Kulmurotov, Sokhibjon (THE INNOVATION ECONOMY, 2026)
This study systematically examines the consolidation and strengthening of beekeeping activities through a cluster mechanism across seven districts of Kashkadarya region: Kitab, Shakhrisabz, Yakkabog, Chiroqchi, Koson, Guzor, and Dehqonobod. The research measured the economic impact of natural differences between mountainous and plain territories, demonstrating that cluster-based association increases productivity by 36–41 percent, boosts export volumes 2.6-fold, and generates over 950 new employment positions. A key deliverable is the “Kitab–Shakhrisabz–Koson Triangle” regional beekeeping cluster project.